HISTORICAL ANALYSIS OF THE FOREIGN AND RUSSIAN VIEWS ON QUALITY MANAGEMENT OF CUSTOMS SERVICES - Yu. E. Gupanova (Russian Journal of Economics and Law, 2012)
The article presents the summarized results of analysis of the foreign and Russian views on the customs services quality management. The evolution of the concepts of general and customs management are defined, as well as the main trends of customs services quality management.